2012
DOI: 10.1021/es301649w
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory FOCUS Surface Water Models Fail to Predict Insecticide Concentrations in the Field

Abstract: The FOrum for the Co-ordination of pesticide fate models and their USe (FOCUS) exposure models are used to predict the frequency and magnitude of pesticide surface water concentrations within the European regulatory risk assessment. The predictions are based on realistic worst-case assumptions that result in predicted environmental concentrations (PEC). Here, we compared for the first time a larger data set of 122 measured field concentrations (MFC) of agricultural insecticides extracted from 22 field studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
86
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(99 citation statements)
references
References 18 publications
12
86
1
Order By: Relevance
“…However, a recent study (18) showed that the FOCUS model, used for the regulatory exposure assessment in the European Union, underpredicts field concentrations of newer, increasingly used insecticides such as hydrophobic pyrethroids. Specifically, the ratio of the predicted insecticide surface water concentrations to the MIC SW was significantly lower for pyrethroids than for organochlorines and organophosphorus insecticides.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a recent study (18) showed that the FOCUS model, used for the regulatory exposure assessment in the European Union, underpredicts field concentrations of newer, increasingly used insecticides such as hydrophobic pyrethroids. Specifically, the ratio of the predicted insecticide surface water concentrations to the MIC SW was significantly lower for pyrethroids than for organochlorines and organophosphorus insecticides.…”
Section: Resultsmentioning
confidence: 99%
“…Targeted postregistration monitoring schemes and regulatory actions are needed, considering that 18 and 24 of the 28 insecticide compounds included in our metaanalysis are currently approved in EU countries and in the United States, respectively. The high numbers of threshold exceedances worldwide are caused by failures of either regulatory exposure assessment (18) or farmers' adherence to prescribed risk management obligations (35).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure models used in RA for predicting concentrations of PPPs in surface waters, for instance, are demonstrated being unreliable for realistic situations (Bach and Hollis, 2012, Knäbel et al, 2012. The application of assessment factors is not sufficient for considering realistic combination effects (Martin et al, 2013).…”
Section: Henrik Sundberg Kemimentioning
confidence: 99%
“…If relevant input parameters may not be correctly estimated or cannot be verified comparing model output (and certainly output from a suite of coupled models), to field measurements raises concerns about its usefulness and validity, especially if contributions from non-modelled point sources cannot be excluded for the field measurements. In addition, if populations of simulations and field measurements are compared, it is crucial to demonstrate that the compared populations of simulations and field measurements represent similar environmental conditions and that for each comparison the application regimes are identical (Knäbel et al, 2012 and two ensuing rebuttals: Bach and Hollis, 2013;Reichenberger, 2013).…”
Section: Resultsmentioning
confidence: 99%